Analisis Kendala dan Peluang Inovasi Dalam Evaluasi Daring Pasca-Pandemi - Mardhia, Dwi; Gunawan, Gunawan; Hermansyah, Hermansyah; Yahya, Fahmi; Sahidu, Hairunnisyah (Indonesian Journal of STEM Education, 2022)
The COVID-19 pandemic necessitated an abrupt shift to online learning, including its evaluation, presenting both challenges and opportunities for innovation in higher education. This study, originally conducted at Universitas Samawa, explored lecturers' and students' profiles and perceptions of online learning evaluations during the pandemic. Findings revealed that WhatsApp was the most dominant platform (76.7%) due to its ease of use, practicality, and accessibility. However, significant obstacles emerged, primarily unstable internet connectivity, especially for students in rural areas, and suboptimal understanding of online learning materials often due to lecturers merely sharing content without in-depth explanations. While online evaluations were perceived as more objective and capable of fostering creativity and critical thinking, concerns regarding academic integrity due to insufficient supervision were also noted. This paper analyzes these identified constraints, juxtaposing them with potential avenues for innovation in online evaluation practices. It argues that addressing connectivity gaps, enhancing pedagogical design for online content delivery, and implementing robust integrity measures are crucial for developing a more effective, equitable, and sustainable online evaluation system in the post-pandemic era.